Artificial Intelligence as a Driver for Women’s Empowerment in Agriculture: A Theoretical Ecosystem for Inclusive Leadership and Sustainable Development - Imane Moutik (Business Ethics and Leadership, 2025)

(untitled)
This theoretical article explores how artificial intelligence (AI) can serve as a transformative framework for empowering rural women and promoting sustainable agricultural development. Grounded in a critical synthesis of peer-reviewed literature, international development reports, and illustrative case studies, the paper introduces a new conceptual model: the AI-facilitated gender empowerment ecosystem (AIGEE). This five-pillar framework integrates technological inclusion, digital literacy, sociocultural adaptation, institutional alignment, and economic empowerment to analyze the conditions under which AI can catalyze gender-equitable transformation in rural agriculture. Drawing on evidence from the Climate Resilient Agribusiness for Tomorrow (CRAFT) initiative in East Africa and a proposed agricultural incubator in Morocco, the study demonstrates how AI-enabled tools, when situated within supportive institutional and community ecosystems, can enhance productivity, reduce environmental risks, and expand women's agency in agrarian value chains. Unlike linear technology diffusion models, AIGEE offers a holistic, context-sensitive digital agriculture approach incorporating intersectional gender analysis and participatory design. The research concludes that AI's potential lies not merely in its technical capacity but in its alignment with inclusive policies, localized knowledge systems, and long-term capacity building. AIGEE contributes to the theoretical literature on gender and technology by framing empowerment as a co-produced outcome of sociotechnical systems rather than a byproduct of access alone. The study invites further empirical research to test and adapt the model across diverse agricultural contexts.